1976
DOI: 10.1007/bf00427285
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of learned taste aversions by pre-exposure to drugs

Abstract: Taste aversions are induced by a variety of psychotropic drugs. In the present experiments taste aversions induced by the barbiturate hypnotic drug, amobarbital, were dramatically reduced by prior exposure to the drug. Increasing numbers of pre-exposures were associated with larger reductions in taste aversions. Reductions in sleeping time (a widely accepted measure of tolerance to barbiturate drugs) were not correlated with reductions in taste aversions. Taste aversions induced by amobarbital were also impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…When keylights did not suppress responding in the present experiments, subsequent attempts to suppress responding in the same birds with combined keylight and hopper-light stimuli paired with d-amphetamine were without effect (P-1210 and P-2408). This is consistent with previous reports showing that prior experience with a drug can attenuate or even prevent suppression by stimuli that are later paired with that drug (Cappell, LeBlanc, & Herling, 1975;Goudie & Thornton, 1975;Vogel & Nathan, 1976). An alternative explanation would be that the effects of prior pairings may influence the ability of other stimuli to suppress responding.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When keylights did not suppress responding in the present experiments, subsequent attempts to suppress responding in the same birds with combined keylight and hopper-light stimuli paired with d-amphetamine were without effect (P-1210 and P-2408). This is consistent with previous reports showing that prior experience with a drug can attenuate or even prevent suppression by stimuli that are later paired with that drug (Cappell, LeBlanc, & Herling, 1975;Goudie & Thornton, 1975;Vogel & Nathan, 1976). An alternative explanation would be that the effects of prior pairings may influence the ability of other stimuli to suppress responding.…”
Section: Discussionsupporting
confidence: 93%
“…This has also been shown for consummatory behavior (Cappell & LeBlanc, 1973;Nathan & Vogel, 1975 (Cappell, LeBlanc, & Herling, 1975;Vogel & Nathan, 1976), prior experience with drug-paired stimuli can also accentuate suppression. The suppression of responding by stimuli paired with 1.0 mg/kg following exposure to stimuli paired with 3.0 mg/kg was durable and persisted until the dose was decreased to .3 mg/kg.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Numerous studies have shown that exposure to either the CS flavor or the US malaise before a conditioning trial attenuates aversion learning. These experiments usually have involved repeated preconditioning presentations of the CS or US event, with at least 24 h between successive preexposures and at least 24 h between the end of the preexposure phase and the subsequent conditioning trial (e.g., Cappell & Le Blanc, 1975;Domjan, 1972; Riley, Jacobs, & LoLordo, 1976;Vogel & Nathan, 1976). Since, typically, 24 h or more intervened between preexposure and conditioning, the resultant interference effects were produced by stim- 133 ulus preexposures which may be characterized as remote from the conditioning trial.…”
mentioning
confidence: 99%
“…It is not only possible to prevent CTA by pre-exposure to the same drug but also by preexposure to a different drug (e.g. Goudie and Thornton 1975;Vogel and Nathan 1976;Braveman 1977;Switzman et al 1981;Bluth6 et al 1985;Rabin et al 1989). …”
mentioning
confidence: 98%